Community based interventions for the prevention and control of Non-Helmintic NTD - Das, Jai K (BioMed Central, 2014)
In this paper, we aim to systematically analyze the effectiveness of community based interventions (CBI) for the prevention and control of non-helminthic diseases including dengue, trypanosomiasis, chagas, leishmaniasis, buruli ulcer, leprosy and trachoma. We systematically reviewed literature published up to May 2013 and included 62 studies in this review. Findings from our review suggest that CBI including insecticide spraying; insecticide treated bednets and curtains; community education and cleanliness campaigns; chemoprophylaxis through mass drug administration; and treatment have the potential to reduce the incidence and burden of non-helminthic diseases. Lack of data limited the subgroup analysis for integrated and non-integrated delivery strategies however, qualitative synthesis suggest that integrated delivery is more effective when compared to vertical interventions; however, such integration was possible only because of the existing vertical vector control programs. Community delivered interventions have the potential to achieve wider coverage and sustained community acceptance. Eradicating these diseases will require a multipronged approach including drug administration, health education, vector control and clean water and sanitation facilities. This would require high level governmental commitment along with strong partnerships among major stakeholders.